Comparative Analysis of Government Systems, Politics, and Economic Policies in Indonesia and China - Wiyana Puspita Ningrum; Yulyana, Eka (Kemudi, 2024)
Every country has advantages and disadvantages regarding the system used in its government. Knowing the government system and various conditions in other countries can help to identify and improve deficiencies in Indonesia. Therefore, the purpose of this study is to compare Indonesia and China in terms of government system, state form, form of government, community conditions, political development, and economic development. The method used is qualitative descriptive with comparative analysis from various reliable sources, and considers relevant literature. The result of this study is that Indonesia uses a presidential system of government and China uses semi-presidential, and the form of the country has something in common, namely a unitary state with its form of government, namely the republic. Meanwhile, the economic development of both countries has had significant growth in recent decades, and its political development Indonesia has undergone a political transformation from authoritarian to democratic rule, while China still runs a one-party system with more focus on economic stability and global influence as well as the condition of its multicultural society with diverse ethnicities, cultures, and religions as well as China also has Cultural diversity, but they tend to uphold Confucian values more It has differences and similarities with its unique factors. So, this study can provide an overview through its comparison from Indonesia and China so that it can see what the advantages and disadvantages of each country are